(untitled) (Revista Contexto & Educação, 2021)
In view of the emerging development of skills related to computational thinking, as well as a variety of research stemming from master’s and doctoral studies developed from graduate programs in Brazil on this theme and the absence of specific studies that portray the current panorama of these studies, this article aimed to identify and characterize studies that focus on the development of computational thinking or that contemplate , in its objectives, the stimulus to such thinking through educational practices, coming from graduate programs in Brazil. For this, a systematic literature review was conducted between 2010 and 2019. Through this research, 71 studies were selected to form the basis of the review, in order to observe the quantitative of research, UF, institutions and graduate programs, approaches and development, educational practices, theoretical-pedagogical assumptions, resources and/or tools used, levels of education, contributions and difficulties reported in implementing use in the context already mentioned.